2011
DOI: 10.1186/1471-2229-11-42
|View full text |Cite
|
Sign up to set email alerts
|

Uncharacterized conserved motifs outside the HD-Zip domain in HD-Zip subfamily I transcription factors; a potential source of functional diversity

Abstract: BackgroundPlant HD-Zip transcription factors are modular proteins in which a homeodomain is associated to a leucine zipper. Of the four subfamilies in which they are divided, the tested members from subfamily I bind in vitro the same pseudopalindromic sequence CAAT(A/T)ATTG and among them, several exhibit similar expression patterns. However, most experiments in which HD-Zip I proteins were over or ectopically expressed under the control of the constitutive promoter 35S CaMV resulted in transgenic plants with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
117
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(121 citation statements)
references
References 75 publications
3
117
1
Order By: Relevance
“…Arce et al have described six motifs associated with the CTRs of HD-Zip I subfamily in signal transduction pathways of different species, which were always ignored in the past. 10) But in this study, the 10 nonidentified motifs were not found to match Arce's results. Therefore, we concluded that the 10 non-identified motifs could have special functions, and this need to be further verified.…”
Section: )contrasting
confidence: 68%
See 3 more Smart Citations
“…Arce et al have described six motifs associated with the CTRs of HD-Zip I subfamily in signal transduction pathways of different species, which were always ignored in the past. 10) But in this study, the 10 nonidentified motifs were not found to match Arce's results. Therefore, we concluded that the 10 non-identified motifs could have special functions, and this need to be further verified.…”
Section: )contrasting
confidence: 68%
“…42) ATHB54 is a atypical HD-Zip I protein with an extremely long CTR (325aa) which a RNA recognition motif can be identified in. 10) In class II, HD-Zip genes of three species were divided into several subclasses as reported in Arabidopsis.…”
Section: Phylogenetic Classification and Structural Analysis Of Slhz mentioning
confidence: 99%
See 2 more Smart Citations
“…HD-ZIP genes play diverse functions in plant development and plant adaptation to environmental stresses (Arce et al, 2011;Brandt et al, 2014). A common feature of HD-ZIP transcription factors is the presence of a leucine zipper (ZIP) domain adjacent to the homeodomain (HD); the HD domain is responsible for the specificity of protein-DNA interactions, and the ZIP domain is important for homo-and heterodimerization.…”
Section: Introductionmentioning
confidence: 99%